PENGARUH PROMOSI DAN SALURAN DISTRIBUSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR PADA PT. CAPELLA DINAMIK NUSANTARA MEDAN - Hernawaty (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2018)
PT.Capella Dinamik Nusantara Medan is a company engaged in the sales of Honda motorcycles, established in 1986 and is a distributor of Honda motorcycles that already has branches in the province of Aceh, Riau and Kepulauan Riau. Some of the problems that occur in the PT. Capella Dinamik Nusantara Medan are relating to the less promotion carried out by the company to attract buyers in making purchasing decisions. Besides, dismissal of the distribution unit for the dealer which is delinquent in payment caused vacuum unit. By considering the use the proper promotion and good distribution channels, it is expected that it will increase the purchasing decision. Based on the brief description, the problem is formulated as follows; how is the effect of promotion and distribution channel on purchasing decisions of motorcycle at PT. Capella DinamikNusantara Medan.The theory used in this research are those of Marketing Management, concerning theory of the Promotion, Distribution Channel, as well as theories of purchase decision.This research used quantitative method and type of research is descriptive quantitative. Data collection was performed by interviews, questionnaires and documentation. Data analysis method used is multiple linear regression analysis. Populations were all dealers of PT. Capella Dynamik Nusantara Medan totaling 104 dealerships. This study used saturated sampling in which 100% of the total population of dealers become 104 respondents and 30 respondents were used to test the validity and the remaining 74 respondents used for sampleAs stated in the hypothesis, the study revealed that the promotion and distribution channels simultaneously and partially had a significant effect on purchasing decisions, and promotion is the most dominant factor affecting purchasing decisions. The test results of determination of R Square is 0.428 which means that 42.8% variable of purchase decision can be explained by the variable promotion and distribution channels. In conclusion, simultaneously and partially promotion and distribution channels had a significant and positive effect on purchasing decisions of motorcycle at PT. Capella Dinamik Nusantara Medan.